Mechanical studies on poly(vinyl chloride)-poly(methyl methacrylate)-based polymer electrolytes - Ramesh, S.; Winie, T.; Arof, Abdul Kariem (Kluwer (now part of Springer), 2010)
The aim of the present work is to study the mechanical properties of poly(vinyl chloride) (PVC)/poly(methyl methacrylate) (PMMA) blends based polymer electrolytes for lithium ion batteries. The introduction of PVC into PMMA is found to increase the Young's modulus value from 5.19 MPa (in pure PMMA) to 6.05 MPa (in PVC:PMMA = 70:30). The different Young's modulus values in PVC blends is due to the difference in the cross-linking density provided by PVC with different weight fraction values. The stress-strain analysis reveals that the mechanical strength of the polymer electrolyte system deteriorated with the incorporation of LiCF(3)SO(3). The results show that the introduction of salt decreases the Young's modulus and stress at peak values along with higher elongation at peak value. The addition of low molecular weight plasticizers to PVC-PMMA-LiCF(3)SO(3) decreases the modulus and stress at peak of the complexes. To be applicable in practical applications, the mechanical strength of the plasticized films is found to improve with the addition of silica as nanocomposite filler.